Comparing the Effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Acceptance and Commitment Therapy Enriched with Compassion on the Components of Dysfunctional Communication Beliefs in Women Seeking Divorce - Farahdel, Somayeh; Mahdian, Hossein; Ghasemi Motlagh, Mehdi (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aims to compare the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Acceptance and Commitment Therapy (ACT) enriched with compassion in altering dysfunctional communication beliefs among women seeking divorce. Methods: Statistical population of this study consisted of all women seeking divorce in District 4 of Tehran city in the year 2021, who were selected from counseling centers supervised by the Organization of Psychology and Welfare through convenience sampling. Next, Eidelson and Epstein’s (1982) Communication Beliefs Questionnaires were distributed for completion, and 45 individuals who scored high on these scales were selected as the sample and randomly placed into two experimental groups and one control group (each group consisting of 15 individuals). For data analysis, descriptive statistical methods (frequency indices, mean, and standard deviation) and inferential statistics (multivariate repeated measures analysis of variance) using SPSS-24 were employed. Findings: Results indicated no significant difference between the ISTDP and ACT enriched with compassion in altering dysfunctional communication beliefs. Both groups showed improvement compared to the control group, but no significant difference was noted between the two in terms of effectiveness. Conclusion: Both ISTDP and ACT enriched with compassion are effective in reducing dysfunctional communication beliefs among women seeking divorce, with no significant difference in effectiveness between the two. This suggests that both therapeutic approaches can be beneficial in this context. Future research should consider broader and more diverse samples, longer follow-up periods, and comparisons to active control groups to further understand the sustained impact and efficacy of these therapies.